Implications of the Theory of Planned Behavior for Green Purchase Intention in Cosmetic Products - Zahro, Fathimatuz; Prihandono, Dorojatun; Yaacob, Zulnaidi; Soliha, Euis (Jurnal Dinamika Manajemen, 2025)
The rising demand for eco-friendly cosmetics in Indonesia reflects a shift in consumer awareness toward sustainability. This study examines the influence of social media marketing, green attitude, and green product knowledge on green purchase intention, with green trust as a moderating variable. Using a quantitative approach, data were collected from 150 consumers of sustainable cosmetic products in Central Java and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that social media marketing, green attitude, and green trust have a significant positive impact on green purchase intention; however, green product knowledge does not have a significant effect. Furthermore, green trust strengthens the relationship between the three independent variables and purchase intention, indicating its moderating role. This research contributes to the development of sustainable marketing strategies, particularly in the cosmetics industry. The findings provide a strategic implication for companies: building authentic consumer trust is paramount and acts as a catalyst to convert positive attitudes and marketing exposure into tangible purchase intentions, thereby supporting the sustainable consumption goals of SDG 12.